What Deters Crime? Comparing the Effectiveness of Legal, Social, and Internal Sanctions Across Countries - Mann, Heather; Garcia-Rada, Ximena; Hornuf, Lars; Tafurt, Juan (Frontiers in Psychology, 2016)
The question of what deters crime is of both theoretical and practical interest. The present paper focuses on what factors deter minor, non-violent crimes, i.e. dishonest actions that violate the law. Much research has been devoted to testing the effectiveness of legal sanctions on crime, while newer models also include social sanctions (judgment of friends or family) and internal sanctions (feelings of guilt). Existing research suggests that both internal sanctions and, to a lesser extent, legal sanctions deter crime, but it is unclear whether this pattern is unique to Western countries or robust across cultures. We administered a survey study to participants in China, Colombia, Germany, Portugal, and USA, five countries from distinct cultural regions of the world. Participants were asked to report the likelihood of engaging in seven dishonest and illegal actions, and were asked to indicate the probability and severity of consequences for legal, friend, family, and internal sanctions. Results indicated that across countries, internal sanctions had the strongest deterrent effects on crime. The deterrent effects of legal sanctions were weaker and varied across countries. Furthermore, the deterrent effects of legal sanctions were strongest when internal sanctions were lax. Unexpectedly, social sanctions were positively related to likelihood of engaging in crime. Taken together, these results suggest that the relative strengths of legal and internal sanctions are robust across cultures and dishonest actions.